Back Cover: Self‐Healing Behavior in a Thermo‐Mechanically Responsive Cocrystal during a Reversible Phase Transition (Angew. Chem. Int. Ed. 1/2017). Issue 1 (15th December 2016) - Liu, Guangfeng; Liu, Jie; Ye, Xin; Nie, Lina; Gu, Peiyang; Tao, Xutang; Zhang, Qichun
Abstract : Coronene–TCNB cocrystals show remarkable self‐healing behavior and thermomechanical responses during reversible single‐crystal‐to‐single‐crystal (SCSC) phase transitions. In their Communication onpage 202 ff., Q. Zhang, X. Tao, et al. show that the global similarity in the packing patterns of the two phases, as well as local differences, such as the molecular stacking sequence and orientation, are the origin of the self‐healing behavior of these crystals.